2020
DOI: 10.1155/2020/8517130
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Overall Survival of Patients with Prostate Cancer in Kyadondo County, Uganda

Abstract: Background. Prostate cancer is the second most common cancer among men globally. A few studies that have been done in Uganda on survival of patients with prostate cancer indicate that, the overall survival of patients with prostate cancer in Uganda is poor. The aim of this study was to determine the 3-year overall survival rate of a cohort of patients with prostate cancer residing in Kyadondo County who were diagnosed from 2012 to 2014. The secondary objective was to correlate the overall survival with the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Bello et al published a small study evaluating factors associated with OS among 48 Nigerian men with metastatic castrate resistant PCa 33 . In a study including both patients with localized and metastatic PCa from Uganda ( n = 36 patients with stage IV disease), Yahaya et al 34 . found that Gleason score and LVI were independent predictors of survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bello et al published a small study evaluating factors associated with OS among 48 Nigerian men with metastatic castrate resistant PCa 33 . In a study including both patients with localized and metastatic PCa from Uganda ( n = 36 patients with stage IV disease), Yahaya et al 34 . found that Gleason score and LVI were independent predictors of survival.…”
Section: Discussionmentioning
confidence: 99%
“… 33 In a study including both patients with localized and metastatic PCa from Uganda ( n = 36 patients with stage IV disease), Yahaya et al. 34 found that Gleason score and LVI were independent predictors of survival.…”
Section: Discussionmentioning
confidence: 99%
“…This observation reflects the spread of PCa from a distance in most of our patients. A Ugandan study reported a 3-year overall survival rate of 67.6% with a median survival of 36.5 months [ 29 ]. These authors had found that Gleason score, clinical stage, and lymphovascular invasion can independently predict the overall survival of the patients with PCa [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Ugandan study reported a 3-year overall survival rate of 67.6% with a median survival of 36.5 months [ 29 ]. These authors had found that Gleason score, clinical stage, and lymphovascular invasion can independently predict the overall survival of the patients with PCa [ 29 ]. Ndoye et al [ 8 ] emphasize not only the delay in diagnosis observed in most sub-Saharan countries but also the lack of policy of channeling these patients suffering from PCa to a center applying the recommendations of learned societies for a codification of management.…”
Section: Discussionmentioning
confidence: 99%
“…Yahaya et al and Okuku et al in two different studies reported 73.1% and 54.8% of patients with PCa in Uganda had Gleason score ≥ 8 [13,14]. In other two studies done in Uganda by Yahaya, it was reported that 44.6% and 55.9% of the patients with PCa had Gleason score ≥ 8 [15,16]. In all the four studies, none of them involved determining of expression of either BRCA1 or BRCA2 protein.…”
Section: Introductionmentioning
confidence: 99%